Experimental characterisation of non-encapsulated bio-based concrete with self-healing capacity. (30th September 2020) - Mohammed, Hazha; Ortoneda-Pedrola, Montserrat; Nakouti, Ismini; Bras, Ana
Highlights: Corrosion in Reinforced Concrete structures occurs due to crack formation within the cover. Non-encapsulated bio-based concrete with self-healing capacity. Bio-mineral is capable of sealing cracks and blocking pores resulting in a delay of water-born ions. Abstract: The main reason for early corrosion in Reinforced Concrete (RC) structures is crack formation within the concrete cover. Cracks can lead to leakage problems, allowing chloride, oxygen, water and other aggressive chemicals to enter into concrete and eventually causes corrosion of steel reinforcement. The paper shows some results of a novel bio concrete with biological self-healing agent, which added into the concrete mixture, autonomously and actively, inhibits the concrete cracks and potential premature reinforcement corrosion. Two compositions of concrete samples were prepared and casted – CEMI and CEMIII with 60% of Ground Granulated Blast Furnace Slag (GGBS) with and without non-encapsulated bio-product utilising iron respiring bacteria. The developed bio-mineral is capable of sealing cracks and blocking pores resulting in a delay of water-born ions in RC structures, acting as a diffusion barrier of oxygen to protect steel reinforcement's passivity towards corrosion. The fresh test results show that these concretes have the potential to be used in RC heavily reinforced and manually compacted sections with vibrations. The water absorption velocity has been significantly reduced with the inclusion of bio-agent in CEMI and CEMIII concretes samples, which was associated with pores sealing. Maximum water absorption via capillary tends to reduce at least 25% when bio-agent was introduced to concrete type CEMIII. Other results emphases the efficiency of the bio-product in CEMIII medium. The bio-agent does not decrease the compressive strength of tested concretes either for CEMI and CEM III. SEM observation shows that the crystals were well developed near the surface of the crack.